Wild Salmon Sustain the Effectiveness of Parasite Control on Salmon Farms: Conservation Implications from an Evolutionary Ecosystem Service. Issue 2 (8th September 2017) - Kreitzman, Maayan; Ashander, Jaime; Driscoll, John; Bateman, Andrew W; Chan, Kai M. A.; Lewis, Mark A.; Krkosek, Martin
Abstract: Rapid evolution can increase or maintain the provision of ecosystem services, motivating the conservation of wild species and communities. We detail one such contemporary evosystem service by synthesizing theoretical evidence that rapid evolution can sustain parasiticide efficacy in salmon aquaculture, thus creating an added incentive for salmon conservation. Globally, wild and farmed salmon share native parasites: sea lice. In most major salmon farming areas sea lice have evolved resistance to parasiticides, but in the North Pacific, where farmed salmon coexist with large wild salmon populations, resistance has not emerged. We present a model to show that flow of susceptible genes from lice hosted on wild salmon to those hosted on farmed salmon can delay or preclude resistance. This theoretical and observational data suggests that wild salmon (both oceanic populations that function as a refuge and local migratory populations that connect this refuge to domesticated environments) provide an evosystem service by prolonging parasiticide efficacy. To preserve this service, aquaculture managers could avoid production quantities that exceed wild salmon abundances, and sustain wild salmon populations through regional and oceanic scale conservation. The evosystem service of resistance mitigation is one example of how a contemporary evolutionary process that benefits people can strengthen the case for conservation of intrinsically important wild species.